Could Age be a potential decelerating factor in clinical orthodontics? - Md Nazmul Hasan; Sheikh Md ShahriarQuader; Md Ali AfzalKhan; Md Mahfuz Hossain (Update Dental College, 2013)
Managing malocclusion by orthodontic treatment require consideration of many factor. One of the important this one is age, as it is the indicator of remaining growth and development of face and jaw and body generally. Clinicians often remain in doubt to plane the orthodontic treatment especially with adult age group. Many biological and psychosocial factors associated with adultsneed a change in biomechanics and treatment approach than that in growing adolescents.This article reports and describesorthodontic management of two adult (from both gender)with modification of conventional approach that manage those successfully. Two years post treatment follow up already ensure stable occlusions and improve quality of life. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15537 Update Dent. Coll. j: 2012; 2 (2): 51-55